Effects of Taurine and Enzymatic Cottonseed Protein Concentrate Supplementation in Low-Fishmeal Diet on Growth, Liver Antioxidant Capacity, and Intestinal Health of Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Zhong Huang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2024)
This study was conducted to investigate the impacts of the dietary addition of taurine and enzymatic cottonseed protein concentrate (ECPC) in low-fishmeal diet on the growth performance, plasma biochemical indices, hepatic antioxidant capacity, intestinal anti-inflammatory capacity, intestinal microflora, and muscle quality of golden pompano (Trachinotus ovatus). A total of three isonitrogenous diets were given to 225 golden pompanos (5.6 ± 0.14 g). They were randomly divided into nine cages (1.0 m × 1.0 m × 1.5 m; three cages per treatment) with equal stocking numbers of twenty-five fish per cage. The results indicated that the CSM-TC group significantly increased the growth performance of juvenile T. ovatus (p < 0.05). The results indicated that compared with other groups, the addition of 1% ECPC and 0.25% taurine has been found to enhance the WGR (weight gain rate), SGR (specific growth rate), and CF (condition factor). Compared with other groups, the relative expressions of GH, GHR1, GHR2, IGF1, IGF2, and MyoG were significantly higher in fish fed with CSM-TC. The results showed that CSM-TC significantly increased the activities of alkaline phosphatase, complement 3, and complement 4 enzymes (p < 0.05). The results showed that dietary CSM-TC increased the activities of hepatic superoxide dismutase and total antioxidant capacity enzymes. Compared with other groups, the hepatic relative expressions of Nrf2, HO-1, and GSH-Px were significantly higher in fish fed with CSM-TC. The results showed that dietary CSM-TC increased the activities of intestinal chymotrypsin, lipase, and α-amylase enzymes. A CSM-TC diet significantly increased the relative expressions of IL-10, ZO-1, Occludin, Claudin-3, and Claudin-15 (p < 0.05). The results showed that CSM-C significantly increased the index of Ace and Chao1 (p < 0.05). In conclusion, a high-fermented cottonseed meal diet can have detrimental effects on physiological health in golden pompano, while adding 1% ECPC and 0.25% taurine can improve hepatic and intestinal health via attenuating inflammation and oxidative stress.